Research on the relationship between key risk factors of university emergencies based on ISM-MICMAC - Yufei Li; Xiaoyun Liu; Nanyan Hu; Xuexue Li (PLoS ONE, 2025)
In order to accurately analyze the interaction among the risk factors of university emergencies, firstly, based on the key performance indicator (KPI) concept, by initially extracting risk factors, identifying initial risk factors, and correcting initial risk factors, and the risk factors of emergencies in universities were divided into three categories: human factors, environmental factors, and management factors, and 18 key risk factors of emergencies in universities, including psychological problems, weak legal awareness and lack of safety awareness, were subdivided and determined. Secondly, the interpretive structure model (ISM) was used to construct a multi-layer hierarchical model of the relationship between university emergencies risk factors, clarified the hierarchical affiliation between the risk factors of university emergencies, divided the risk factors of university emergencies into surface direct factors, middle indirect factors and deep fundamental factors, and analyzed the coupling effect of various risk factors on university emergencies. Thirdly, combined with the matrix impacts cross-reference multiplication applied to a classification (MICMAC), the driving force and dependence force of each risk factor of university emergencies were obtained, and the risk factors of university emergencies were divided into spontaneous factors, independent factors, dependent factors, linkage factors, etc. 4 categories, and targeted governance and prevention measures were proposed for different types of risk factors. Finally, the research results will help universities to accurately identify, warn and manage the key risks of emergencies, and provide a reference for the management of emergencies in universities.